2018
DOI: 10.24903/jam.v2i2.375
|View full text |Cite
|
Sign up to set email alerts
|

PKM Buah Naga Merah Di Kecamatan Samboja Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur

Abstract: Pelatihan ini dilaksanakan dalam rangka Program Kemitraan Masyarakat, dengan sasaran adalah masyarakat Kecamatan Samboja khususnya warga Desa Wonotirto dan Desa Beringin agung. Pelatihan dilakukan dalam lima (5) tahap. Metode pelatihan budidaya ini dengan melakukan pelatihan dan penyuluhan kepada peserta tentang budidaya tanaman buah naga merah, penanganan virus dan penanganan paska panen, proses pembuatan sirup dan ice cream dari daging buah naga merah, proses pengolahan saos dan saos pedas dari limbah kulit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The previous study conducted by Yulian (2018) demonstrates that the oil palm plantation has provided prosperity for the rural household, but what happens is a long process of livelihood vulnerability and dependency toward income gained from the salary in oil palm plantation. Similarly, Wijaya (2013) also found that the inland fisherfolk community in the MMA is experiencing extreme vulnerability. Amalia (2019) found that the losses of livelihood diversity cause such vulnerability.…”
Section: The Rationale Of Studymentioning
confidence: 85%
See 1 more Smart Citation
“…The previous study conducted by Yulian (2018) demonstrates that the oil palm plantation has provided prosperity for the rural household, but what happens is a long process of livelihood vulnerability and dependency toward income gained from the salary in oil palm plantation. Similarly, Wijaya (2013) also found that the inland fisherfolk community in the MMA is experiencing extreme vulnerability. Amalia (2019) found that the losses of livelihood diversity cause such vulnerability.…”
Section: The Rationale Of Studymentioning
confidence: 85%
“…Palm oil is planted in the swampy area or even in the peatlands (Wijaya 2013) and riparian buffer zone in which, based on land use and spatial planning, some of its parts are categorized as a conservation area. Palm oil plantation activities such as land clearing, seeding, planting, nursing, harvesting, and processing contribute to pollution of waterways for aquatic life through pesticide and fertilizer (Agency 2018, Glinskis andGutiérrez-Vélez 2019) and frequent flooding (Colchester, Chao et al 2011).…”
Section: The Rationale Of Studymentioning
confidence: 99%